(untitled) (Journal of Renal and Hepatic Disorders, 2020)
The Severe Acute Respiratory Syndrome Coronavirus 2 is a recent disease that originated in China by the end of 2019. The origins of the dis-ease can be traced to bats, but it has been transmitted to humans, and the inter-human transmission is particularly rampant which has led to a pandemic of unseen proportions. The organ principally involved is the lungs, and severe pneumonia with lack of oxygen leads to fatalities. The aim of this review was to study the involvement of the kidneys with regard to COVID-19 infection and how the disease may affect people on hemodialysis or those who have undergone a kidney transplant. Indeed, the virus, in addition to the lungs, may affect other vascularized organs to a common receptor on lung epithelium and the endothelium of any organ. The kidney, which has a large endothelium surface, is affected, and COVID-19 may lead to acute renal failure. On the other hand, the virus may easily spread among people who are on hemodialysis three times a week. People on hemodialysis may have low immunity, and the virus may have dangerous effects on such people. Finally, renal transplant patients may be easily affected, and the virus may have severe consequences, even death. We will summarize the principal prophylactic measures to be adopted and the therapeutic measures available. Clearly due to the recent occurrence of the pandemic the majority these measures lack a basis in evidence-based medicine and only highlight the efforts to limit COVID-19 induced damage.